2007
DOI: 10.1007/s11249-006-9181-x
|View full text |Cite
|
Sign up to set email alerts
|

Electron stimulated decomposition of fluorocarbons on amorphous hydrogenated carbon (a-CHx) overcoats used in data storage media

Abstract: The electron-induced surface chemistry of perfluoropolyalkylether (PFPE) lubricants on a-CH x films has been probed by studying the impact of free electrons on perfluorodiethylether, (CF 3 CF 2 ) 2 O, and 2,2,2-trifluoroethanol, CF 3 CH 2 OH, as models of the chemical functionality of PFPE lubricants such as Fomblin Zdol. Electron-stimulated decomposition of (CF 3 CF 2 ) 2 O and CF 3 CH 2 OH on fresh and oxidized a-CH x is observed when the sample is unbiased and in the presence of 70 eV free electrons. Electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(44 reference statements)
1
2
0
Order By: Relevance
“…The net observation is that the changes in the C 1s feature of the a -CF x film are consistent with a net increase in the oxidation state of the surface atoms. This is consistent with XPS studies of the oxidation of a -CH x films which reveal the appearance of high binding energy features during the course of oxidation. , In the case of the a -CF x film, the changes can be resolved into the changes in the concentrations of the different components of the film.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The net observation is that the changes in the C 1s feature of the a -CF x film are consistent with a net increase in the oxidation state of the surface atoms. This is consistent with XPS studies of the oxidation of a -CH x films which reveal the appearance of high binding energy features during the course of oxidation. , In the case of the a -CF x film, the changes can be resolved into the changes in the concentrations of the different components of the film.…”
Section: Resultssupporting
confidence: 85%
“…An ion gauge was used to determine the pressure as O 2 was being introduced into the chamber but was then turned off immediately afterward to avoid the influence of electrons, ions, or excited state neutrals emitted from the ion gauge. In prior work studying the oxidation of a -CH x films, it was discovered and reported that the oxidation kinetics are sensitive to the ions and free electrons that are generated by the ion gauge used to measure O 2 pressure. The same effect was observed when using a -CF x films, and so the uptake curves reported in Figure were all obtained with the ion gauge on for only 30 s every 30 min. This was determined to be sufficiently short that it did not influence the oxidation of the surface.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation